Carrying javanese local wisdom in mathematical mode - Mustafa, M.; Prabowo, A.; Sukono, .; Ngadiman, . (2019)
People of Cikakak Traditional Village, Wangon District, Banyumas Regency, Central-Java Province are known as the followers of Islam Aboge (Alif Rebo Wage). Their religious holidays such as the beginning of fasting month (Ramadan) and Eid al-Fitr are determined based on the rules they have been using so far, namely Month Code or Sandi Bulan and Year Code or Sandi Tahun. This research is conducted using literature study method and field study in the form of interview with respondents. This research aims at producing a mathematical model which matches the function of these two codes. The results obtained are five mathematical equations to determine the names of year, saptawara and pancawara days for the 1st day of each month, and saptawara and pancawara days for other dates.